Development of digital modules to optimize Basic Japanese online learning - Via Luviana Dewanty; Ghaida Farisya (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
Many Japanese language learning modules have been prepared or developed independently by each department or study program. To get a new Japanese learning experience, students need learning media that present interesting and up-to-date, which can be accessed online anytime, anywhere. Interactive online modules are one of the media that can make this happen. Students can download and access the online module as an ebook via their PCs, laptops, or devices. The online module materials have links directly connected to explanation videos related to basic Japanese. In each chapter of the material, there are also interactive quizzes that can test students' insights. The method used in this research is Reeves' DBR (Design-Based Research) model, which consists of four phases. Phase 1 is in the form of identifying material, media, and module needs through interviews. Phase 2 is creating and preparing online modules following the syllabus for the basic Japanese course material. Furthermore, in phase 3, the module was tested twice on students who chose the basic Japanese courses. In phase 4, the trial data will be analyzed, and then it will be explained whether the online module that has been developed can be used in learning Basic Japanese. The results of the questionnaire in the trial showed that all aspects of the assessment received good responses and were included in the high category so that the module could be used in online elementary-level Japanese learning. Even so, it still needs several revisions and refinements related to evaluation questions and the content of the module's material before it can be implemented in learning in the following years. AbstrakBanyak modul pembelajaran bahasa Jepang yang telah disusun maupun dikembangkan mandiri oleh tiap jurusan atau program studi. Untuk mendapatkan pengalaman belajar bahasa Jepang baru, pemelajar memerlukan media pembelajaran yang menyajikan materi-materi menarik dan up to date, yang dapat diakses secara daring kapan saja, di mana saja. Modul digital interaktif adalah salah satu media yang dapat mewujudkan hal tersebut. Modul digital berupa ebook dapat diunduh dan diakses pemelajar melalui PC, laptop, maupun gawai masing-masing. Materi-materi dalam modul digital memiliki tautan-tautan yang terkoneksi langsung ke video-video penjelasan terkait bahasa Jepang dasar, dan di tiap chapter materi terdapat pula kuis-kuis interaktif yang dapat menguji wawasan pemelajar. Metode yang digunakan dalam penelitian ini adalah DBR (Design Based Research) model Reeves yang terdiri dari empat tahap. Tahap 1 berupa identifikasi kebutuhan materi, media, dan modul melalui wawancara. Tahap 2 adalah pembuatan dan penyusunan modul digital sesuai dengan silabus materi mata kuliah-mata kuliah bahasa Jepang dasar. Selanjutnya pada tahap 3, modul diujicobakan sebanyak dua kali pada mahasiswa yang mengontrak mata kuliah-mata kuliah bahasa Jepang level dasar. Pada tahap 4, data uji coba akan dianalisis dan kemudian akan dipaparkan apakah modul digital yang telah dikembangkan dapat digunakan dalam pembelajaran bahasa Jepang dasar. Hasil angket pada uji coba menunjukkan bahwa semua aspek penilaian mendapat respon baik dan termasuk kategori tinggi, sehingga modul dapat digunakan dalam pembelajaran daring Bahasa Jepang tingkat dasar. Meski begitu, masih perlu beberapa revisi dan penyempurnaan kembali terkait soal-soal evaluasi dan isi materi pada modul sebelum dapat benar-benar diimplementsikan dalam pembelajaran di tahun-tahun berikutnya.Kata Kunci: Bahasa Jepang; modul digital; pembelajaran daring